Effect of Biden’s administration on international students’ choice of major and long-term career planning - Claudia Salvador Camacho (UNC Test Journal, 2025)
This paper analyzed the impact of the more restrictive temporary non-immigrant H-1B work visa policy implemented in the 2004 Visa Reform Act on international students’ choice of major and long-term career planning, specifically focusing on how Biden’s presidency (2021–2024) influenced these decisions after the restrictive policies had already been enforced. Using a Difference-In-Difference (DIF) regression approach, the study compared international students before and during Biden’s administration, utilizing data from an international enrollment liberal arts college in the U.S. while controlling for gender, country of origin, high school Grade Point Average (GPA), Scholastic Aptitude Test (SAT)/ American College Test (ACT) scores, scholarship status, and student-athlete participation. The results indicated that students affected by Biden’s presidency were less likely to choose a Science, Technology, Engineering, and Mathematics (STEM) major by approximately 35 percentage points, potentially due to expectations of looser H-1B visa policies reducing the perceived necessity of pursuing a STEM degree to secure a work visa. Additionally, the COVID-19 pandemic and the shift to remote learning diminished the appeal of studying abroad, particularly for STEM fields that required hands-on experience. The findings also revealed that females and scholarship recipients were more likely to choose STEM majors by 6.5 and 4.8 percentage points, respectively, while Europeans and student-athletes were less likely by 12.9 and 22.8 percentage points. Despite these shifts, the relaxation of visa policies did not compromise the academic quality of international students, as higher high school and SAT/ACT scores remained strong predictors of selecting a STEM occupation.